‘Poor little princess’: Queen Victoria’s Court as a Site of Imperial Conquest - Chandrica Barua (Cahiers Victoriens et Edouardiens)
This essay illuminates the elusive and messy archives of an unusual presence in the Victorian court, that of Princess Victoria Gouramma (1841‒1864), daughter of the deposed King of Coorg, Chikka Virarajendra and goddaughter and namesake of Queen Victoria. The messy and circuitous archives of Gouramma reveal the story of a colonized, racialized, exteriorized colonial subject becoming an ornamental interior of the Empire. Gouramma had found herself in 1850s England, displaced from her homeland and culture, anglicized and Christianized, pruned and displayed as the glorious civilizational project of the Empire, and yet never truly being an inhabitant of Victorian interiors. Queen Victoria’s royal court, within which Gouramma’s material and ephemeral presence is articulated, was fashioned as a sanctuary from the ‘savage’ and ‘primitive’ colony of Gouramma’s past. In this unique instantiation of imperial conquest founded upon care and rehabilitation, we are prompted to rethink not only the colonial civilizational agenda but also the contentious intimacies amongst the Empire and its colonies. Through an analysis of the recorded and recollected interactions between the Queen and her Indian ward, this essay charts out the emergence of a maternal politics—care and conquest—that wielded a specific epistemological, ontological power and an insidious psychic conquest of personhood.